2009
DOI: 10.1002/ejoc.200900770
|View full text |Cite
|
Sign up to set email alerts
|

A Tris‐Macrocycle with Proton Sponge Characteristics as Efficient Receptor for Inorganic Phosphate and Nucleotide Anions

Abstract: International audienceSynthesis, characterisation and proton-sponge behaviour of a new linear constrained tris-macrocycle (L), containing three cyclen (cyclen = 1,4,7,10-tetraazacyclododecane) reinforced macrocycles connected by two 2,6-pyridinediylbis(methylene) linkers, is reported. Protonated forms of L are efficient receptors for inorganic phosphate and nucleotide anions (ATP and ADP). The binding properties of L toward these substrates have been investigated in aqueous solution by means of potentiometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…Accordingly, molecular modelling studies performed on the 1 : 1 adducts formed between (H 3 46) 3+ and (H 4 46) 4+ and (HATP) 3À or ADP 3À showed that the phosphate chain of both nucleotides is partially enclosed within the cleft delimited by the two lateral protonated cyclen units, but does not interact with the central macrocyclic moiety. 67 The nucleobase seems to play a minor role in the stabilization of the adducts.…”
Section: Cyclic Receptors Containing More Than One Aromatic Unit or C...mentioning
confidence: 99%
“…Accordingly, molecular modelling studies performed on the 1 : 1 adducts formed between (H 3 46) 3+ and (H 4 46) 4+ and (HATP) 3À or ADP 3À showed that the phosphate chain of both nucleotides is partially enclosed within the cleft delimited by the two lateral protonated cyclen units, but does not interact with the central macrocyclic moiety. 67 The nucleobase seems to play a minor role in the stabilization of the adducts.…”
Section: Cyclic Receptors Containing More Than One Aromatic Unit or C...mentioning
confidence: 99%
“…Selective syntheses also gave access to more rigid compounds, currently named constrained-or reinforcedmacrocycles, by binding two opposite nitrogen atoms by an alkyl bridge, such as ethylene or propylene chains. [14][15][16][17][18][19][20][21][22][23] These crossbridged ligands may adopt conformations where all four nitrogen lone pairs point inside of the cavity upon metal complexation. Moreover, the short bridging chain induces further rigidity in the ligand and forces the nitrogen lone pairs into a cis-folded geometry which promotes distorted coordination modes, such as tetrahedral, pseudo-octahedral, distorted trigonal-bipyramidal or distorted square pyramidal.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, cross-bridged tetraazacycloalkanes are often presented as proton sponges. [14][15][16][17][18][19][20][21][22][23] These ligand geometrical features also lead to particular kinetically inert metal complexes, [14][15][16][17][18][19][20][21][22] extending the applications of some tetraazacycloalkane derivatives to positron emission tomography ( 64 Cu-labelled macrocycles) or therapeutic purposes ( 67 Cu-radioactive pharmaceuticals). [24][25][26][27][28] However, the main drawback of such ligands for these applications is undoubtedly, still yet, their low kinetic complexation process with the targeted metals.…”
Section: Introductionmentioning
confidence: 99%
“…A tris-macrocylic compound where three cyclen macrocycles reinforced with ethyl bridges are linked in a linear arrangement by two pyridyl units L 8 has been reported. 21 This molecular scaffold acts as a double proton sponge that cannot be deprotonated even at very high pH and the binding of phosphate species ADP and ATP was investigated. A related compound, the tetra-zinc(II) complex of a linked linear tetra-cyclen supramolecular chelator L 9 , synthesised using a protection/ deprotection strategy, was shown to act as a template to induce aggregation of double stranded DNA inhibiting the action of other DNA binders.…”
Section: Tetraaza Macrocycles: Cyclenmentioning
confidence: 99%